Analysis Incentive Of Employee Work Spirit PT. Indomarco Prismatama Lampung Branch - hujaimatul fauziah; Maruli Susanto Effendi (Saburai International Journal of Social Sciences and Development, 2018)
This study aims to analyze the Incentives for the Work Spirit of PT. Indomarco Prismatama Lampung Branch. The analytical method used: simple regression. From the results of the t test, the value of  thitung = 11,479.  lebih dari ttabel 2,66 hypothesis states that there is an influence between the Incentive variable (X) on the Work Spirit (Y) of employees at PT. Indararco Prismatama Lampung Branch.The coefficient of determination was obtained R2 = 0.8682 = 0.754 = 0.754 x 100 = 75.4%. means that the Incentive variable explains variations in changes to the variable Work Spirit on employees of PT.Indomarco Prismatama Lampung Branch by 75.4%, while the remaining 24.6% is influenced by other factors not explained in this study. The regression equation between the Incentive variables to Work Spirit is Y = 11,158 + 0,729X which means that every increase of one point than the Incentive variable will be followed by an increase in the Work Spirit variable of PT. Domarco Prismatama Branch Lampung Lampung employees by 0,729 points.